An Analysis of Translating Collocation Problem on Undergraduate Thesis Abstract of The English Education Study Program - endang lestariana (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2017)
Present-day, an attractive issue related to language producing phenomenon from source language into target language was frequently happened. Translating collocation in undergraduate thesis abstract often faced the problems. Consequently, the first language acquisition influenced the students’ translating production. The students could not achieve the same competence of second language acquisition. Therefore, the present study tried to investigate the students’ translating collocation problem. The primary aim of this research was to describe the output of translating collocation on undergraduate thesis abstract of the English Education Study Program of STAIN Jurai Siwo Metro Lampung. This research applied qualitative research in the form of embedded research. In collecting the data applied documentation and interview. Purposive sampling was used as the technique for choosing the participant. The participants of this research were ten students who had written undergraduate thesis abstract of the English Education Study Program of STAIN Jurai Siwo Metro Lampung in the academic year of 2013/2014 M. The research findings showed that the Indonesian collocation was translated into English collocation on undergraduate thesis abstract consisted of the incorrect collocation 74,45% and correct collocation 25,55%. There were two types of incorrect collocation namely lexical collocation 89,01% and grammatical collocation 10,99%. Moreover, problems that were faced by the student in translating collocation were caused by approximation, ignorance of the rule restriction, overgeneralization, interlingual transfer, false concept of hypothesized, the use of synonym, word coinage and the meaning of lexical item. The solutions of this problem were the usage of appropriate Collocation Dictionary and learned deeply about collocation. Therefore, the students should be more active to increase their English proficiency and the lecturers had better often give the feedback on their translating production to avoid translating collocation problem. Keyword: Approximation, Collocation, Translation, Abstract.